Advancing Industry through Design: A Longitudinal Case Study of the Aviation Industry - Rebecca Anne Price; Christine De Lille; Katinka Bergema (She Ji: The Journal of Design, Economics and Innovation, 2019)
Design educators and industry partners are critical knowledge managers and co-drivers of change, and design graduate and post-graduate students can act as catalysts for new ideas, energy, and perspectives. In this article, we will explore how design advances industry development through the lens of a longitudinal inquiry into activities carried out as part of a Dutch design faculty-industry collaboration. We analyze seventy-five (75) Master of Science (MSc) thesis outcomes and seven (7) Doctorate (PhD) thesis outcomes (five in progress) to identify ways that design activities have influenced advances in the Dutch aviation industry over time. Based on these findings, we then introduce an Industry Design Framework, which organizes the industry/design relationship as a three-layered system. This novel approach to engaging industry in design research and design education has immediate practical value and theoretical significance, both in the present and for future research. Keywords: System, Scale, Design, Impact, Methodology, Innovation